Effectiveness of the Combination of Spirulina platensis and Stichopus variegatus on Prevention of Caspase-3 Gene Expression of Dementia Rat Models - Safira, Rizka; Botutihe, Lisa Agustina; Yuliani, Sapto; Kintoko, Kintoko (Sanata Dharma University, 2024)
The death of cells in the brain, especially the hippocampus, manifests in a decrease in memory, language, and behavior. Golden sea cucumber (Stichopus variegatus) andblue-green algae (Spirulina platensis) are reported to have high antioxidant content which has the potential to prevent cell death in the brain due to oxidative stress thereby preventing memory decline.This study aimed to investigate the effect of the combination of Stichopus variegatus and Spirulina platensis on preventing caspase 3 gene expression in pyramidal hippocampal cells in a rat model of trimethlytin-induced dementia (TMT). This study used Sprague Dawley rats, about 2 months old, weighing 180-200 g, divided into 6 treatment groups, with each group consisting of 8 rats. The hippocampus was taken from the right cerebral hemisphere for histological observations of pyramidal caspase-3 gene expression in the CA1 and CA2-CA3 regions.The combination of Spirulina platensis and Stichopus variegatus with a dose 200 mg/kg BB can prevent the expression of caspase-3 in the CA1 and CA2-CA3 areas of the hippocampus. Conclusion: The combination of spirulina and golden sea cucumber extracts has the potential to prevent caspase 3 gene expression in pyramidal cells of TMT-induced dementia rat models.